Analisis Kualitas Soal Asesmen Sumatif Akhir Semester Bahasa Jawa Kelas VII di SMPN 2 Kutowinangun - Cahyani, Anggilia Dwi; Sukoyo, Joko (Universitas Nusantara PGRI Kediri, 2025)
This research was aims to determine the quality of the Javanese final summative assessment questions for grade VII even semester at SMPN 2 Kutowinangun 2023/2024. This research used descriptive quantitative method with interview and study of document as data collection technique. The data source used in this research consisted of question sheets and 30 answer sheets wich taken randomly. The analysis of question was used SPSS dan anates. The results of this research showed (1) there are three questions should be revised because the construction is not complete; (2) based on validity, 57,14% questions was valid and 42,86% questions was invalid; (3) reliability of objective questions is very high, but the reliability of the essay questions is low; (4) difficulty level of the questions is not in balance proportion, so it needs to be revised; (5) based on descrimination level, 71,43% of questions was suitable; and (6) there found 9 questions with effective distractor, whereas 10 questions was not have effective distractor.